Agentive suspension of oppressive structures: self-concept and emotion-work among Muslim mothers who study at a Jewish university. Issue 7 (3rd October 2018) - Shoshana, Avihu; Shchada, Sahar
ABSTRACT: This article aims to highlight the significance of self-concept and emotion-work in the everyday experiences of Muslim mothers who are students at a Jewish university. This research objective was achieved by means of in-depth interviews with mothers who are all studying to earn master's degrees. Our study reveals three main findings. The first is an 'inundated self' that experiences frequent phenomenological preoccupation with the dialectic between structure and agency, as well as acute internal transitions between space-affiliated self-concepts, thus making it difficult to establish narrative coherence. The second is the agentive suspension of the structure. And last is the emotion-work (characterized by experiences of aloneness, which is dissimilar from loneliness) and management of emotional tension. The discussion section suggests pondering the unique interaction between structure and agency, especially the agentive strategies that enable creative inventions.